Creating meaningful practice : a study on meaning making and communicational practice in a municipal organization - Ek, Sarah (SLU/Dept. of Urban and Rural Development, 2014)
This thesis investigates and analyzes, with the help of the theoretical concept of Communities of Practice (CoP) the communication practice of an environmental organization in Sweden. The practice under investigation is a unit which is part of a municipal organization that works strategically with environmental issues, in order to achieve environmental goals set by the politicians of the municipality. Civil servants, that is, the members of the practice, have an ambition to increase and improve their communication. The problem is that the members of the practice perceive the communication that they carry out and their communication skills to be insufficient. With the concept of CoP and by focusing on two central components of the concept of “practice” and “meaning” this thesis investigates how the civil servants view their practice and what meanings they create on communication. This is in order to highlight what underlying assumptions the civil servants might have when it comes to their practice and their task to carry out communication. Furthermore, this thesis finds out what aspects of their meaning of communication that are reified and what aspects that are open for new meaning creation. The study reveals that there exist diverse meanings within the environmental unit, on what communication means. Moreover, the study identifies a norm within the practice, indicating that to be a member of the practice it is important being ambitious and passionately engaged in environmental issues. The study also reveals a dominant aspect of an underlying assumption implying that an increased communication will turn the environmental unit´s practice into a more effective and successful one. A conclusion that is drawn is that the meaning of communication, created by the members of the practice is reified. Nevertheless, the norm and assumption that exist in the practice, implying that every member has to be engaged in environmental issues is open for new meaning creation, it is problematized by the members of the practice themselves. These findings might be helpful for the members of the practice in order to clarify and identify what obstacles they need to manage in order to develop and improve their communication practice. The study contributes to the research of focusing on communication practices within municipal organizations and presents a picture of what obstacles civil servants working within the environmental field have to tackle in their practice.